2020
DOI: 10.1111/mcn.12986
|View full text |Cite
|
Sign up to set email alerts
|

The significance of early breastfeeding experiences on breastfeeding self‐efficacy one week postpartum

Abstract: Many new mothers do not reach their breastfeeding goals. Breastfeeding self‐efficacy is a modifiable determinant influenced by prior and new breastfeeding experiences. More knowledge about factors associated with early breastfeeding experiences and breastfeeding self‐efficacy would allow us to qualify breastfeeding counselling and increase breastfeeding duration. This study aimed to identify prevalence and factors associated with early negative breastfeeding experience, low breastfeeding self‐efficacy in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Moreover, although these problems can be alleviated by educating women on effective breastfeeding techniques, it is often difficult for postpartum women in rural areas to obtain relevant counseling and guidance [ 46 ]. When breastfeeding problems arise but cannot be solved in a timely and effective manner, postpartum women’s BSE decreases, and mothers may eventually give up breastfeeding [ 47 ]. Therefore, public health services in rural China should focus on helping new mothers resolve early problems they encounter during the breastfeeding process, especially insufficient milk, poor sucking or latching, and slow milk secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although these problems can be alleviated by educating women on effective breastfeeding techniques, it is often difficult for postpartum women in rural areas to obtain relevant counseling and guidance [ 46 ]. When breastfeeding problems arise but cannot be solved in a timely and effective manner, postpartum women’s BSE decreases, and mothers may eventually give up breastfeeding [ 47 ]. Therefore, public health services in rural China should focus on helping new mothers resolve early problems they encounter during the breastfeeding process, especially insufficient milk, poor sucking or latching, and slow milk secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Multiparous women who have positive or negative experiences can influence their intention and self-efficacy to their next child (Kronborg, Foverskov, Vaeth, & Maimburg, 2018). Other studies have shown that between negative experiences and lower self-efficacy, is more substantial in primparous women than in multiparous women (Nilsson, Kronborg, Rahbek, & Strandberg-Larsen, 2020).…”
Section: B Experiencementioning
confidence: 99%
“…Privacy experience is defined as the social media user having experienced a privacy violation or invasion. Bandura (1977) concluded that negative experience with a task reduces the individual’s self-efficacy regarding that task; and this relationship has subsequently been found in a wide array of settings, including information-search self-efficacy (Giallo and Little, 2003; Chiou and Wan, 2007), maternal self-efficacy (Harries and Brown, 2017), teaching self-efficacy (Norris et al , 2018), academic self-efficacy (Falconer and Djokic, 2019), information privacy self-efficacy (Chai et al , 2009) and others (Kvasková and Almenara, 2021; Nilsson et al , 2020). The same relationship between self-efficacy and experience is likely true for social media users who have experienced privacy violations.…”
Section: The Model and Hypothesesmentioning
confidence: 99%